KONSEP JIHAD: ANTARA NORMATIFITAS DAN HISTORISITAS - Affy Khoiriyah (Fakultas Agama Islam Universitas Wiralodra, 2020)
Abstract This article aims to analyze the problem of the contradictions of Muslims' understanding of the concept of jihad which has ben impicated on different implementations. Every Muslim believe in the importance of jihad as one of the principles of Islam, because in the belief of every Muslim, the teachings of jihad are inward in it and every Muslim is automatically a mujahid. moreover, because of the multi-interpretative characteristics of Islam, there has never been a single view of how to properly interpret jihad. In fact, throughout the history of Islamic civilization, there are two different spectrums of thought about jihad. Both recognize the importance of jihad as one of the principles of Islam, but both have different interpretations of jihad. The difference is based on how to interpret religious texts related to jihad. Once the text is central to the formulation of the concept of jihad in Islamic history, it is no doubt that the text is used and misused, interpreted and interpreted in order to support and justify the agendas of certain groups. Therefore, the interpretation of the jihadic texts must be carried out comprehensively and not ignoring the historical socio and socio political background of the text, so that it can be fully absorbed in the understanding of jihad.